TRANSISI PENGGUNAAN BAHASA ASING DI ABAD 21; SEBUAH KECENDERUNGAN GLOBAL - Wahyuningsih, Noverita (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2006)
Up to the end of the twentieth century, Arabic and English have played an important role as the media for communication all over the world. Both languages are significantly used in not only national but also global scopes. Millions of people in the world today use either passive or active Arabic and/or English in their daily lives. The question is,’ will the global community in the 21st century still put these international languages in a position as important as it is today?’ Trends in the use of languages in the world can be viewed from several different aspects, among which are the economic strength of a language and the demography of language users. Although so far there has been no fixed agreement on the criteria of a language to be called as “the world language” yet, there is a tendency that by mid 21st century there will be trends in the world’s language domination and hierarchy. The trends will also involve the global use of Arabic and English. The two languages are predicted to still have an essential position as the world’s major languages and therefore will be used globally. The use of Arabic and English is strongly predicted to undergo a transition in a positive way. In addition to that, it is not impossible that by mid 21st century, there will be a tendency of bilingual education (using foreign languages in presenting non-linguistic school subjects) spreading in the world’s urban areas, including those areas in Indonesia.